PENGARUH PENERAPAN STANDAR AKUNTANSI PEMERINTAHAN, SISTEM PENGENDALIAN INTERNAL, DAN PEMANFAAT TEKNOLOGI INFORMASI TERHADAP KUALITAS LAPORAN KEUANGAN - Anggita Nur Setyarini; Sri Ambarwati; Nelyumna (Fakultas Ekonomi dan Bisnis Universitas Pancasila, 2024)
Abstract This study aims to test whether there is an effect of applying government accounting standards, internal control systems, and the use of information technology on the quality of the financial reports of the local government of Serang City. The technique used in determining the sample is purposive sampling. The number of samples in this study were 80 people with a total of 39 OPD. The type of data used in this research is primary data. And data collection used in research is by survey method using a questionnaire. The analytical method used is multiple linear regression analysis using the SPSS version 27 program. The test results state that: (1) There is an influence between the application of government accounting standards and the quality of the financial reports of the local government of Serang City. (2) There is an influence between the internal control system and the quality of the financial reports of the regional government of Serang City. (3) There is no effect of the use of information technology on the quality of the financial reports of the regional government of Serang City. Keywords : Government Accounting Standards, Internal Control Systems, Quality of Government Financial Reports, Utilization of Information Technology